The Use of AI and Technology Tools in Developing Students’ English Academic Writing Skills - Zulfa, Siti; Dewi, Ratna Sari; Hidayat, Didin Nuruddin; Hamid, Farida; Defianty, Maya (Proceeding International Conference on Education, 2023)
The rapid advancement of technology tools, particularly Artificial Intelligence (AI), has led to the integration of technology-assisted learning media into educational settings. This study focuses on the utilization of AI and technology tools by students in the process of English academic writing and its impact on their writing skills. Employing a qualitative approach, data was gathered through open-ended questionnaires and semi-structured interviews involving 73 English education students at an Islamic University in Indonesia. The findings of the study revealed that students employed a total of 15 technology tools, categorized into four types: language structures, sources, saving tracks, and references. According to the participants, the tools used by the participants were able to provide: direct feedback and correction, writing skills development. Specifically, the participants claimed that the tools enhance their understanding of grammatical rules and vocabulary acquisition. In addition, the participants considered that the tools help them to write a more cohesive and coherent essay. This study implies that the incorporation of technology tools in English academic writing has the potential to revolutionize the development and evaluation of writing skills. However, it is essential for students to strike a balance between leveraging these tools and honing their writing skills to ensure writing development.